Primary Amenorrhea, Aplastic Uterus, and a Functional Vagina: A Rare Case of Mayer-Rokitansky-Küster-Hauser Syndrome - Gregory W. Kirschen; Natalie Semenyuk (Hindawi Limited, 2019)
Background. Müllerian agenesis, also known as Mayer-Rokitansky-Küster-Hauser syndrome (MRKHS), a failure of female urogenital development, typically results in a completely stenotic or rudimentary dimple vagina, both of which are generally nonfunctional in adulthood without mechanical dilation or surgical reconstruction. Case. A 20-year-old Tanner stage V heterosexual woman with normal sexual function since coitarche presented with a chief complaint of primary amenorrhea. She was found to have aplastic uterine buds, absent endometrium/cervix, normal ovaries, and an unusually well-developed lower vagina, a rare presentation of MRKHS. We discuss mechanisms by which the anomaly may have arisen. Summary & Conclusion. This case thus expands the clinical presentation of MRKHS to include a normal appearing vagina with intact sexual function from first sexual encounter, raising interesting questions about the basic underlying embryology.